Trajectories of depressive and anxiety symptoms in older adults: a 6-year prospective cohort study - Holmes, S.; Esterlis, I.; Mazure, C.; Lim, Y.; Ames, D.; Rainey-Smith, S.; Fowler, C.; Ellis, K.; Martins, R.; Salvado, O.; Doré, V.; Villemagne, V.; et al. (Wiley Interscience, 2018)
Copyright © 2017 John Wiley & Sons, Ltd. Objective: Depressive and anxiety symptoms are common in older adults, significantly affect quality of life, and are risk factors for Alzheimer's disease. We sought to identify the determinants of predominant trajectories of depressive and anxiety symptoms in cognitively normal older adults. Method: Four hundred twenty-three older adults recruited from the general community underwent Aß positron emission tomography imaging, apolipoprotein and brain-derived neurotrophic factor genotyping, and cognitive testing at baseline and had follow-up assessments. All participants were cognitively normal and free of clinical depression at baseline. Latent growth mixture modeling was used to identify predominant trajectories of subthreshold depressive and anxiety symptoms over 6 years. Binary logistic regression analysis was used to identify baseline predictors of symptomatic depressive and anxiety trajectories. Results: Latent growth mixture modeling revealed two predominant trajectories of depressive and anxiety symptoms: a chronically elevated trajectory and a low, stable symptom trajectory, with almost one in five participants falling into the elevated trajectory groups. Male sex (relative risk ratio (RRR) = 3.23), lower attentional function (RRR = 1.90), and carriage of the brain-derived neurotrophic factor Val66Met allele in women (RRR = 2.70) were associated with increased risk for chronically elevated depressive symptom trajectory. Carriage of the apolipoprotein epsilon 4 allele (RRR = 1.92) and lower executive function in women (RRR = 1.74) were associated with chronically elevated anxiety symptom trajectory. Conclusion: Our results indicate distinct and sex-specific risk factors linked to depressive and anxiety trajectories, which may help inform risk stratification and management of these symptoms in older adults at risk for Alzheimer's disease. Copyright © 2017 John Wiley & Sons, Ltd.